2021
DOI: 10.4103/jfmpc.jfmpc_2583_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 treatment in children

Abstract: Background: Exact information about the efficacy of various medications proposed by regulatory bodies in children with COVID-19 is limited due to the lack of controlled trials in the existing literature. Methods: Different electronic databases (MEDLINE, EMBASE, Web of Science, COCHRANE CENTRAL, LitCovid, medRxiv, and bioRxiv) were searched for articles describing the management of COVID-19 cases in children with 18 shortlisted medications. Prospective/retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 83 publications
0
15
0
4
Order By: Relevance
“…Most children have milder COVID-19 than adults do, and a small percentage of children require treatment, so few meta-analyses on pediatric treatment have been reported. A systematic review and meta-analysis on the treatment of COVID-19 in children showed that anti-inflammatory agents such as corticosteroids and antivirals such as RDV are the most promising for severe cases of pediatric COVID-19 [ 37 ]. In addition, WHO and various guidelines based on large RCTs and systematic reviews suggest that in addition to RDV, corticosteroids, IVIG, tocilizumab, anakinra, infliximab, aspirin, and heparin, other drugs cannot be recommended in cases of COVID-19 in children of any severity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most children have milder COVID-19 than adults do, and a small percentage of children require treatment, so few meta-analyses on pediatric treatment have been reported. A systematic review and meta-analysis on the treatment of COVID-19 in children showed that anti-inflammatory agents such as corticosteroids and antivirals such as RDV are the most promising for severe cases of pediatric COVID-19 [ 37 ]. In addition, WHO and various guidelines based on large RCTs and systematic reviews suggest that in addition to RDV, corticosteroids, IVIG, tocilizumab, anakinra, infliximab, aspirin, and heparin, other drugs cannot be recommended in cases of COVID-19 in children of any severity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average LOS for those who used steroids was 4.9 days, while those who did not use steroids stayed for 6.5 days. A meta-analysis was done regarding the use of antivirals in treatment regimens of COVID-19 in the pediatric age group, and it showed that antivirals were administered in 15.3% of children, and remdesivir was the most often used antiviral medicine in 6.2% of included children, with no major side effects [ 25 ]. Recent studies have indicated that remdesivir should be used only in severe situations, even in adults.…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro estudio, 40,4% de los pacientes pediátricos con COVID-19 recibieron corticoides intrahospitalariamente, incluyendo el 28,1% de los casos asinhttps://doi.org/10.17843/rpmesp.2023.401.12326 tomáticos. Sin embargo, una revisión sistemática en niños encontró que la mayoría de casos asintomáticos no recibió tratamiento alguno (8) . Nuestros hallazgos al respecto requieren futuras indagaciones, pues es posible que parte de estos participantes hayan requerido recibir corticoides debido a condiciones concomitantes.…”
Section: Discussionunclassified